(untitled) (Marketing Journal, 2025)
This study presents the results concerning the key issues of the organization and management of innovation activities in the healthcare system at the regional level. The main purpose of the work was to create and scientifically substantiate a conceptual model of innovation management in regional healthcare, as well as to introduce organizational mechanisms for its implementation and evaluate their effectiveness in the field of medical and diagnostic technologies. The objectives of the study included an anal ysis of the state of the existing organizational system, identification of problems hindering development, identification of prospects, and justification of necessary changes in the field of innovation in healthcare and medical science at the regional level. 303